2007
DOI: 10.1097/mlg.0b013e31804b1ae7
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in the Neurofibromatosis Type 2 Patient: Long‐Term Follow‐up

Abstract: Early surgical intervention for vestibular schwannomas in NF2 patients when the cochlear nerve can be spared is an important consideration to allow for possible cochlear implantation. A 6- to 8-week recovery period for the anatomically intact cochlear nerve may be necessary to obtain a positive promontory stimulation response following tumor resection and should be performed prior to cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
106
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 15 publications
2
106
0
1
Order By: Relevance
“…In Type I Neurofibromatosis, 90% of the patients develop at least one-sided VS. Ten times less frequent is the neurofibromatosis type 2 which is associated with bilateral VSs in 90% of the affected patients 2,9 . Considering the large number of the affected patients, early diagnosis and treatment of the disease is mandatory in order to achieve favourable results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Type I Neurofibromatosis, 90% of the patients develop at least one-sided VS. Ten times less frequent is the neurofibromatosis type 2 which is associated with bilateral VSs in 90% of the affected patients 2,9 . Considering the large number of the affected patients, early diagnosis and treatment of the disease is mandatory in order to achieve favourable results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more and more CIs are an option for the treatment of hearing loss for these patients. Several studies suggest a very good hearing rehabilitation of acoustic neuroma patients after CI 9,17,18 . However, nearly all studies are limited due to small patient numbers 19,20 -reporting case files or groups of up to 3 patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,5 Reports of cochlear implant use in patients with neurofibromatosis type 2 have shown that they are superior to brainstem implants for increasing auditory abilities and for sustaining these results in the long term. 2,5 Therefore, cochlear implants have become an option in such circumstances. The indispensable condition for this approach is that the anatomy and function of the cochlear nerve be preserved.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of preserving the cochlear nerve in neurofibromatosis cases makes it feasible to fit cochlear implants for improved auditory rehabilitation. 2,4,5 We present the results attained in a patients with neurofibromatosis in whom the neoplasm was removed and a cochlear implant was placed simultaneously. Based on a review of the literature, this is the first documented case of this procedure in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Functional results show great variability; from noise perception only to useful speech discrimination in audiovisual mode in a few patients so far. Since the early trials by Hitselberger and House in 1979, as reported by Edgerton et al 13 and Hit sel berger et al, 21 profound improvements in implant array, technology, and speech processing strategies 65 have brought about useful improvement in functional outcome, 4,8,9,17,23,29,31,32,37,42,43,45,46,48,58,59 but still results remain less favorable than in cochlear implants or auditory brainstem implants (ABIs) in patients without NF2. 8 Visionindependent speech perception is not generally achieved.…”
mentioning
confidence: 99%